(untitled) (Research, Society and Development, 2021)
Maternal death is defined as that which occurs during pregnancy or up to 42 days after delivery and has a direct or indirect relationship with this process. Due to its avoidability it is considered a serious violation of human rights. This study aims to analyze the cases of maternal mortality in Aracaju from 2010 to 2018, according to their causes, sociodemographic, obstetric characteristics and geographic distribution. This is an ecological study, territorially based, of the temporal series type, carried out in Aracaju/SE, using as a sample the data obtained through the Municipal Epidemiological Surveillance and DATASUS referring to maternal deaths that occurred in the municipality from 2010 to 2018. For statistical analysis, the Software R was used and QGIS 3.8 was used for the mapping of deaths. The Maternal Mortality Ratio remained unstable during the analyzed period. The year 2015 had the lowest rate and 2011 the highest. The sociodemographic profile shows that the majority were black/brown, single, with schooling from 8 to 11 years of schooling and only housewives. The mean age was 29.47 years. A significant number of deaths were related to direct obstetric causes. Most occurred in the puerperium, in public establishments and were classified as probably preventable. The North and West zones concentrated a higher occurrence of cases. Maternal mortality in the municipality remained above the average recommended for the country, with emphasis on direct obstetric causes and the predominance of the black/brown population that draws attention to the vulnerability of this group.